1997
DOI: 10.3109/10799899709036604
|View full text |Cite
|
Sign up to set email alerts
|

MSH Receptors and the Response of Human A375 Melanoma Cells to Interleukin-1β

Abstract: alpha-Melanocyte-stimulating hormone (alpha-MSH, alpha-melanotropin) has been shown to be an inhibitory factor in many immunologic and inflammatory processes involving the cytokine interleukin-1 (IL-1). As the mechanism of the interaction between IL-1 and alpha-MSH at the receptor level is unknown, we have studied the role of MC1 melanocortin receptors in two variants of the human melanoma cell line A375 differing in their sensitivity to the cytostatic effects of IL-1 beta. Both IL-1 sensitive (A375r-) and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A375 malignant melanoma cells were transfected to stably overexpress MC1R for evaluation of the MC1R imaging probes both in vitro and in vivo. The A375 malignant melanoma cell line was chosen due to its very low endogenous expression of MC1R, , providing both low- and high-expressing cells for the in vitro as well as in vivo selectivity studies. qRT-PCR of A375 and A375/MC1R cells revealed the level of MC1R mRNA expression to be ∼100-fold higher in the engineered cells compared to the parental cell line.…”
Section: Resultsmentioning
confidence: 99%
“…A375 malignant melanoma cells were transfected to stably overexpress MC1R for evaluation of the MC1R imaging probes both in vitro and in vivo. The A375 malignant melanoma cell line was chosen due to its very low endogenous expression of MC1R, , providing both low- and high-expressing cells for the in vitro as well as in vivo selectivity studies. qRT-PCR of A375 and A375/MC1R cells revealed the level of MC1R mRNA expression to be ∼100-fold higher in the engineered cells compared to the parental cell line.…”
Section: Resultsmentioning
confidence: 99%
“…Five MC receptor subtypes have been cloned to date (MC-1R-MC-5R) with MC-1R reported to be the subtype expressed exclusively on the surface of melanocytes and melanoma cells (Mountjoy et al, 1992). The MSH receptor status for the cells used in this study have previously been investigated (Ghanem et al, 1988;Goodall et al, 1994;Baumann et al, 1997). The HBL cell line typically expresses 2000-3000 MSH binding sites per cell (Ghanem et al, 1988), in contrast with the A-375SM cell line where 600 sites per cell are usual (Baumann et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…The MSH receptor status for the cells used in this study have previously been investigated (Ghanem et al, 1988;Goodall et al, 1994;Baumann et al, 1997). The HBL cell line typically expresses 2000-3000 MSH binding sites per cell (Ghanem et al, 1988), in contrast with the A-375SM cell line where 600 sites per cell are usual (Baumann et al, 1997). It is of note that a strong positive correlation exists between the proportion by which NF-κB was inhibited at a given α-MSH concentration in these two cell types and the above reported receptor numbers.…”
Section: Resultsmentioning
confidence: 99%
“…However, stable transfection of these cells with the wildtype MC-1R showed that these cells were then able to respond to a-MSH with a significant reduction in invasion. The HBL melanoma cell line has previously been demonstrated to express 1000 -3000 MSH receptor-binding sites per cell , and A375 and C8161 melanoma cell lines have also been demonstrated to have MSH receptors (Baumann et al, 1997) and MSH binding sites (Sharma et al, 1996). In comparison, normal human cutaneous melanocytes are reported to express between 300 and 1000 binding sites per cell (Donatien et al, 1992;De Luca et al, 1993).…”
Section: Discussionmentioning
confidence: 99%